Identification of D/Yama2019 Lineage-Like Influenza D Virus in Chinese Cattle - Yu, Jieshi; Li, Tianyu; Wen, Zhenyu; Wu, Siyu; Wang, Zhilin; Zheng, Jiaying; Chen, Mingwang; Chen, Faming; Wei, Wen-Kang; Zhai, Shao-Lun; Liao, Ming (Frontiers in Veterinary Science, 2022)
Outbreaks of influenza D virus (IDV) continue to be reported in many countries. On the basis of the hemag-glutinin-esterase fusion (HEF) gene, five IDV genetic lineages have been identified: D/OK, D/660, D/Yama2016, D/Yama2019 and D/CA2019 lineages. Previously reported IDV strains in China all form a sub-clade (D/China sub-lineage) within D/OK lineage. From October 2021 to February 2022, nasal swab samples (n = 250) were collected from apparently healthy cattle in slaughterhouses around the city of Guangzhou, China, and screened for IDV by RT-PCR. Ten samples were positive for IDV. An IDV strain with nearly complete genome sequences was identified and designated as D/bovine/CHN/JY3001/2021. Importantly, sequence alignments and phylo-genetic analyses revealed that this IDV strain is genetically close to the strains (>98% homology) in the D/Yama2019 lineage that has been found only in Japan, but distant from the previously reported Chinese IDV strains ( 95% similarity). These results demonstrate the emergence of D/Yama2019 lineage IDV in Chinese cattle herds, highlighting a need for future surveillance of D/Yama2019-like viruses toward better understanding both epidemiology and diversity of IDV in China.